A MODIFIED Z-SOURCE HALF BRIDGE CONVERTER FOR PHOTOVOLTAIC APPLICATIONS - Mr. Sachin S. Kumbhar; Prof. P. Sharath Kumar (International Journal of Innovations in Engineering Research and Technology, 2021)
Now a day’s the rate of energy generated by the renewable energy sources are increasing rapidly. More popular source form these sources is the photovoltaic system source, but this photovoltaic system is now also most costly and a research work is going on to reduce the cost and increase efficiency of photovoltaic system. Half bridge converter system is developed for to convert dc power in to the ac and also boost dc output. Due to less no of switches, complicity of converter has been reduced.